Pengaruh Kualitas Pelayanan, Lokasi dan Persepsi Harga terhadap Kepuasan Pelanggan di Restaurant The Cutler Prime Rib - Ajri Putra Kurnia; Jamaludin Khalid (Journal Social Society, 2026)
The culinary industry, particularly premium restaurants, faces increasing competition as customers evaluate not only food quality but also service quality, location convenience, price perception, and overall dining experience. This study aims to analyze the effect of service quality, location, and price perception on customer satisfaction at The Cutler Prime Rib. This research used a quantitative approach with a survey method. The population consisted of customers of The Cutler Prime Rib, while the sample included 100 respondents who had visited the restaurant at least twice. The respondents were selected using purposive sampling. The research instrument was a structured questionnaire using a five-point Likert scale, and data were collected through questionnaire distribution. Data were analyzed using SPSS, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that service quality has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.506, t-value of 5.362, and significance value of 0.000. Location also has a positive and significant effect, with a regression coefficient of 0.233, t-value of 2.865, and significance value of 0.005. Meanwhile, price perception does not have a significant partial effect, with a regression coefficient of 0.084, t-value of 1.040, and significance value of 0.301. Simultaneously, the three variables significantly affect customer satisfaction, as indicated by an F-value of 41.428 and significance value of 0.000. The R² value of 0.564 indicates that 56.4% of customer satisfaction is explained by the independent variables. These findings imply that restaurant management should prioritize service quality improvement, maintain location advantages, and align prices with perceived customer value. In conclusion, customer satisfaction at The Cutler Prime Rib is mainly influenced by service quality and location.